Development of Flap Books as an Alternative for Non-Electronic Science (Biology) Learning Media - Fadlilah, Dina Rahma; Murdiono, Seno; Susanti, Baiq Hana (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2022)
Background: Nowadays, utilization of electronic-based learning media (such as internet network, computer, HP) has been significantly increase. However, it has limitations such as electrical disruptions that might occur in schools, unstable internet networks. A teacher has to enforce learning media so that the learning process continues to run attractively and remain meaningful. This study aims to develop a flap book on excretory system material in grade 8 (VIII) SMP / MTs. Methods: The development of this flap book follows Sugiyono's development model. The stages of the model are the identification of potential and problems, data collection, product design, design validation, design revisions, product trials, product revisions, product trials, product revisions. Results: Based on the results obtained from the validation carried out by media experts and material experts, the flap book developed is suitable as a learning media with very good categories. Assessment by teachers received very good results with a percentage of 94.7%. Assessment by students received very good results with a percentage of 91%. Conclusion: Based on the validity test, the flap book deserves to be used as learning media with a very good category. Keywords : Flap book, Science (Biology) Learning Media, Non-electronic